Ultra-low flow rate measurement techniques. (December 2021) - Graham, Emmelyn; Thiemann, Kerstin; Kartmann, Sabrina; Batista, Elsa; Bissig, Hugo; Niemann, Anders; Boudaoud, Abir Wissam; Ogheard, Florestan; Zhang, Yu; Zagnoni, Michele
Abstract: This paper outlines the state-of-the-art techniques to measure ultra-low flow rates down to 5 nL/min that have been developed by eight European organisations in an EMPIR collaborative research project. The techniques include gravimetric, optical interface tracking, optical pendant drop, micro Particle Image Velocimetry (μPIV) and displacement methods. The measurement principles, experimental setup, results and measurement uncertainties are summarised. The techniques and uncertainties developed are currently being validated through an intercomparison exercise using three transfer standards. This comparison will test steady flows and fast changing flow rates. The new techniques developed will be used to test and calibrate medical infusion devices, micro- and nano-fluidic systems and other ultra-low flow rate devices such as perfusion systems for organ-on-a-chip applications.